Value Added Tax (VAT): The impact on the chain producer, processor, trader, consumer, state budget - Mircea Toma (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
Counteracting the crisis, theoretically but also practically cannot ignore the direct and consequential effects (collateral) of taxes and contributions due to the state budget and distribution of profits, on the chain: Financial Institutions -> Suppliers of inputs -> Agricultural producers -> Wholesalers -> Processing industry -> En-detail traders -> Consumer -> State budget. Solutions require transparency, solidarity, equity, social justice in the distribution of efforts and usufruct (profit) on all chain participants to achieve useful goods and services useful for the human society. An orderly adjustment of tax and contribution system may lead to the adoption of those measures to stimulate domestic consumption, domestic output growth and rotation speed of capital, reducing the budget deficit, uncontrolled growth of prices, inflation and unemployment, in a word of imbalances in economic life. To assess the impact of VAT on the chain was started from two hypotheses : rethinking the VAT quota level on the chain and determine and regularization of the VAT, by entitling the right to the users of agricultural production to deduct VAT from the price paid to individual producers (associated )namely calculating VAT from 100 price paid . The results are concretized in: increasing revenues ( about 2.4 billion / year), reducing the public institutions spending on goods and services bearing VAT by 20% (about 2oo million Euro/ year ), reduction of VAT refunds from the budget, reducing the gap between theoretical and potential VAT collected from 42 % (49.5 % ) to 24%, by increasing the collection from 58% (50.5 %) to 76 %, concentration collecting VAT chargeable (76,22 %) from merchants and diminishing the amount of payment by the economic operators on channel.
Keywords: 330; VAT; chain; VAT quota; tax evasion; state budget